Effects of physical charges on uric acid, creatinine and urea in college athletes - Chávez Hernández, Jaime Patricio; Sánchez Anilema, José Alfredo; Ortiz Fernández, Danilo; Bonifaz Arias, Iván Giovanny; Palacios Valdiviezo, Dennys Germán; Santillán Obregón, Rodrigo Roberto (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Metabolic indicators are biochemical markers that help to identify the health effects or not of physical stimulus, helping to make decisions related to directing specific sports training process and educational process in general. Objective: To analyze values of renal profile (uric acid, creatinine and urea) in athletes of the Centro de Educación Física de la Escuela Superior Politécnica del Chimborazo (ESPOCH). Methods: A representative sample (99 subjects, both sexes) of university athletes was studied, studying some renal indicators (uric acid, creatinine and urea) of interest to determine the assimilation levels in physical load. Results: The average value obtained in uric acid was 4.2 mg/dL (Normal Level), the average value in creatinine of 0.6 mg/dL, with 10 subjects qualified qualitatively with a Low level (9.09%) and the rest with a qualitative qualification of Normal level, while the average value in urea was of 25.9 mg/dl (Normal Level). The linear correlations established between the three metabolic variables studied showed a weak positive influence. Conclusions: The indicators obtained show a correct adaptation to physical load in university athletes under study, except for some particularities to be taken into account.